A thermodynamic and exergoeconomic numerical study of two-stage annular thermoelectric generator. (25th June 2019) - Asaadi, Soheil; Khalilarya, Shahram; Jafarmadar, Samad
Highlights: A three-dimensional model of a two-stage ATEG is established. Thermodynamic and exergoeconomic performance of the two-stage ATEG is investigated. The comparison of results for different geometrical parameters is conducted. Two-stage ATEG leads to better energy and exergy performance. The single-stage ATEG performs more economical than the two-stage ATEG. Abstract: A three-dimensional simulation of a two-stage annular thermoelectric generator is conducted to investigate the thermodynamic and the exergoeconomic performance of the thermoelectric device. The simulations are carried out considering the influence of Thomson effect and temperature-dependent material properties of thermoelectric legs to improve the precision of the study. The effect of two geometrical parameters, the height ratio of thermoelectric stages and angle ratio of legs as well as the influence of heat source temperature on the energy, exergy and economic performance of two-stage ATEG is studied. Results indicate that for a range of heat source temperatures, the output power, conversion efficiency and exergy efficiency of two-stage ATEG are higher compared to single-stage ATEGs based on the low-temperature and high-temperature materials. Moreover, the exergoeconomic study reveals that the single-stage ATEG performs more economical than the two-stage ATEG in all of the studied heat source temperatures. The amount of heat source temperature has a direct influence in determining the proper height ratio to reach the maximum thermodynamic and exergoeconomic efficiencies. Also, it is found that the angle ratio of 1 leads to better energy and exergy performance and least unit cost of output power.